Raj od dewelopera. Kulturowy obraz wspólnot mieszkaniowych na nowych osiedlach - Magdalena, Szczepańska (Studia Etnologiczne i Antropologiczne, 2013)
The advertisements of new housing estates convince us of a new quality of the flat environment. The aim of the text is to present a cultural image of new housing estates of blocks of flats built after 2000. A dominant organizational form are housing cooperatives there. They were described through the prism of the organizational culture. The analysis of the content of opinions on the housing cooperative Internet fora was made, namely the analysis of the topics important for inhabitants, methods of their joint actions, norms binding in these communities and ways of taking social control. The studies included 30 opinions from the housing cooperative Internet fora from Gdańsk, Poznań, Warsaw, Wrocław and Łódź.